The Role of the Clergymen in Creating a Model of Submissive Femininity in Philanthropic Work in Nineteenth-Century Britain - SAHLI , Fatiha (Journal of Human Sciences, 2025)
This study suggests that the clergymen in nineteenth-century Britain supported women’s involvement in charitable work to cultivate a submissive, nurturing model of femininity that complemented patriarchal male norms. Although some historians have argued that Christianity played a crucial role in shaping women’s social experience, this article puts forward some arguments to prove the opposite. Rooted in Christian doctrine, many clerics promoted the idea of women as naturally subordinate to men, both in the family and in society. The patriarchal interpretation of religious teachings reinforced the idea that women’s primary virtues were piety, modesty, and submission, often influencing the expectations placed on women participating in philanthropic efforts. Further, they shaped a model of female philanthropy that emphasised submission and moral duty over independence and social change, keeping women within a framework that prevented them from challenging the broader patriarchal structures of the time. The analysis showed that the clergymen framed women’s philanthropic work as virtuous, yet at the same time, they reinforced societal norms that limited their independence and enhanced their subordinate position.